RISIKO USAHATANI JAGUNG HIBRIDA DI DESA LENTENG TIMUR, KECAMATAN LENTENG, KABUPATEN SUMENEP - Zakiyyah, Ela Muthi'atin; Destiarni, Resti Prastika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Maize production in Lenteng Timur Village fluctuates every year with an average decrease of 38%. The decline indicates that there are problems faced by farmers in running their farms. The purpose of this research is to identify risk events and risk sources, and analyze the risks using the House of Risk (HOR) model at the level of hybrid maize farmers in East Lenteng Village. This research was conducted from September - November 2022 with the object of research are hybrid maize farmers in East Lenteng Village. 43 farmers were selected by purposive sampling based on Lemeshow formula. The analysis method used was the House of Risk (HOR). The results of the HOR Phase 1 analysis show that there are 13 Risk Events and 9 risk sources (Risk Agent) which are then prioritized into 5 priority risk sources for further mitigation action. In the HOR Phase 2 analysis, there are 5 mitigation strategies for handling priority risks. These mitigation strategies can be carried out to reduce losses during the hybrid maize production process.